2020
DOI: 10.1167/jov.20.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of content and viewing distance on the preferred size of moving images

Abstract: While visual size preferences regarding still objects have been investigated and linked to the "canonical size" effect-where preferred on-screen size was significantly related to objects' real-world size-the visual size preferences related to moving images of natural scenes has not been researched. In this study, we measured the preferred size of moving images of natural scenes and short duration and investigated the effect of viewing distance on size preferences. Our results showed that the preferred size var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to the sense of "being-there" and "reality," which were considered during the design, viewers of UHD images have often reported strong impressions such as "beautiful," "powerful," and "delicious." Previous studies have suggested that the viewing environment, such as the viewing distance and screen size, contributed to these impressions [10]. As it can be assumed that the viewing distance and position vary significantly, particularly when viewing in a living room, these findings also suggest that the producer's intentions represented in the video content may not be appropriately delivered to the viewers, depending on the viewing conditions.…”
mentioning
confidence: 89%
“…In addition to the sense of "being-there" and "reality," which were considered during the design, viewers of UHD images have often reported strong impressions such as "beautiful," "powerful," and "delicious." Previous studies have suggested that the viewing environment, such as the viewing distance and screen size, contributed to these impressions [10]. As it can be assumed that the viewing distance and position vary significantly, particularly when viewing in a living room, these findings also suggest that the producer's intentions represented in the video content may not be appropriately delivered to the viewers, depending on the viewing conditions.…”
mentioning
confidence: 89%